2015
DOI: 10.3109/0886022x.2015.1040698
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent high-volume hemofiltration promotes remission in steroid-resistant idiopathic nephrotic syndrome

Abstract: Inflammation is a key part in the etiology and progression of idiopathic nephrotic syndrome (INS), we hypothesize that removing pro-inflammatory cytokines with intermittent high-volume hemofiltration (IHVHF) could improve the outcome in INS patients. The purpose of the current study is to examine whether IHVHF promotes remission in steroid-resistant INS. Fifty-one steroid-resistant INS patients were followed up on an open-label basis with prospective evaluations. Thirty-five patients received mycophenolate mof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Our studies indicated that only serum IL‐8 levels were significantly increased in patients with steroid‐resistance when compared to steroid‐sensitive INS. Further studies indicated that intermittent high‐volume haemofiltration (IHVHF) promoted remission in steroid‐resistant INS patients with volume overload and accompanied with IL‐8 serum levels decreased, therapeutic efficacy of IHVHF may partly be due to serum IL‐8 clearance. However, whether IL‐8 levels can be used to evaluate the prognosis of IMN remains unknown.…”
supporting
confidence: 46%
“…Our studies indicated that only serum IL‐8 levels were significantly increased in patients with steroid‐resistance when compared to steroid‐sensitive INS. Further studies indicated that intermittent high‐volume haemofiltration (IHVHF) promoted remission in steroid‐resistant INS patients with volume overload and accompanied with IL‐8 serum levels decreased, therapeutic efficacy of IHVHF may partly be due to serum IL‐8 clearance. However, whether IL‐8 levels can be used to evaluate the prognosis of IMN remains unknown.…”
supporting
confidence: 46%
“…During peritoneal equilibrium test, peritoneal cavity fluid was collected and spun down to remove cellular debris, and then the supernatants were frozen at −80 °C until assay of monocyte chemoattractant protein-1 (MCP-1) by Enzyme-linked immunosorbent assay (ELISA) with ELISA kits (R&D System, Minneapolis, MN) as describled in our previous study [ 19 ].…”
Section: Measurement Of Mcp-1mentioning
confidence: 99%
“…The fact that all patients recruited in this study were not taking any steroid treatment for a period of at least 2 months, there would be an enhanced risk of inflammation and production of certain proinflammatory cytokines, which are known to activate NOX (22). The efficacy of steroids and immunosuppressive treatments in INS implies the involvement of cytokines and immunogenic molecules in pathophysiology of the disease (23). An increase in the expression of Toll-like receptors and interleukin-6 has been linked to INS pathogenesis, and activation of NADPH oxidase has been independently reported to occur through Toll-like receptors and cytokines (24,25).…”
Section: Discussionmentioning
confidence: 99%